GeoGebra, a dynamic software for conceptual understanding and visualisation - Multi-directionality of influence - Bayaga, A. (South African Journal of Higher Education, 2024)
This study delves into the dynamic interplay between GeoGebra, a prominent interactive digital tool, and science, technology, engineering, and mathematics (STEM) cognition, focusing on teachers. Anchored by the objective to unravel how GeoGebra influences conceptual understanding and visualisation, the research hypothesises that GeoGebra significantly influences cognitive outcomes in STEM cognition. Thus, aiming to assess the hypothesis that GeoGebra significantly influences cognitive outcomes, a Multi-Group Analysis (MGA) using Partial Least Squares-Structural Equation Modelling (PLS-SEM) was employed. Data was collected through a survey designed to capture the experiences and interactions of 71 teachers with GeoGebra. The significant direct pathways (Analogical Comparison Principle (ACP) and Error and Misconceptions Reflection Principle (EMR) and between Mathematical and Computational Algorithms (MCA) and Analogical Comparison Principle (ACP)) established empirical evidence to the theory that GeoGebra can facilitate conceptual understanding as well as cognitive development. Additionally, the indirect pathways with no significant effects such as Mathematical Cognition (MAS) to ACP to EMR was indicative of the fact that influence of GeoGebra operates more through direct interactions with the software as opposed to through mediated learning processes. The conclusion is that influence of GeoGebra is not uniform across all contexts, indicative of the fact that factors such as geographical location play a critical role in shaping the software’s effectiveness in enhancing STEM education. In sum, while GeoGebra is a potent interactive digital tool for enhancing STEM cognition, the results call for tailored strategies in integrating digital tools like GeoGebra, by considering the specific needs of different learning context